Pengembangan Kamus Saku Bahasa Arab pada Aplikasi Mobile Legends - Deraya, Ahdiyaka Sani; Zukhaira, Zukhaira (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to develop a pocket Arabic dictionary for Mobile Legends as a practical medium to assist users in understanding Arabic vocabulary in the game interface and to support informal vocabulary learning in a digital context. This study employed a Research and Development (R&D) method using a modified 4D model consisting of three stages: define, design, and develop. The population of this study was Mobile Legends players in Semarang City, with a sample of 20 respondents selected using purposive sampling based on specific criteria related to gameplay experience. Data were collected through questionnaires, expert validation sheets, and interviews. The data were analyzed using descriptive quantitative and qualitative techniques to obtain comprehensive findings. The results of the needs analysis showed that 70% of respondents had difficulty understanding Arabic vocabulary in the game interface. Based on these findings, a pocket dictionary containing selected game-related vocabulary was developed as a practical reference tool. The product was validated by an Arabic language expert and a media expert, resulting in an average score of 94, categorized as highly feasible. These findings indicate that the developed pocket dictionary effectively supports vocabulary comprehension and enhances informal learning in digital game-based environments.